2014
DOI: 10.1002/jcb.24870
|View full text |Cite
|
Sign up to set email alerts
|

Influence of kinin peptides on monocyte-endothelial cell adhesion

Abstract: Adhesion of leukocytes to vascular endothelium in response to proinflammatory mediators is an important component of the overall inflammatory reaction. In the current work, we used a retinoic acid-differentiated human promonocytic cell line, U937 and a human microvascular endothelial cell line, HMEC-1 to analyze the effect of the potent pro-inflammatory bradykinin-related peptides (kinins) on cell adhesion. Bradykinin (BK) and kinin metabolites without the C-terminal arginine residue enhanced adhesion of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Ju et al (2000) reported an increased pSTAT3 level in bovine aortic endothelial cells 5 minutes after B2R activation. Similar results, with a maximal response after 15 minutes of BK-induction, were obtained in studies performed on a human microvascular endothelial cell line (Guevara-Lora et al, 2014). In this study, we demonstrated enhanced STAT3 phosphorylation after the 15-min treatment with BK, but it was significantly reduced after the co-stimulation with BK and SUM (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Ju et al (2000) reported an increased pSTAT3 level in bovine aortic endothelial cells 5 minutes after B2R activation. Similar results, with a maximal response after 15 minutes of BK-induction, were obtained in studies performed on a human microvascular endothelial cell line (Guevara-Lora et al, 2014). In this study, we demonstrated enhanced STAT3 phosphorylation after the 15-min treatment with BK, but it was significantly reduced after the co-stimulation with BK and SUM (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…These observations correlate with the finding discussed above and corroborate the protective role of D2R agonists in the inhibition of pro-inflammatory processes induced by BK in the vascular system. However, additional studies analyzing the B1R involvement should be conducted, since this receptor has a great importance for leukocyte adhesiveness during chronic inflammation (Figueroa et al, 2015) and is concurrently able to regulate STAT3 activation in monocytes (Guevara-Lora et al, 2014). Although the influence of D2R on the regulation of STAT3 phosphorylation has been reported (Kim et al, 2010;Qiu et al, 2016), our study showed no significant changes in the level of this parameter.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…In pathological conditions, a rise in the level of bradykinin in the respiratory system causes acute respiratory distress syndrome (ARDS, a form of acute lung injury), dry cough, inflammation, and apoptosis via release of proinflammatory mediators such as cytokines (TNF-α and interferon-γ) and chemokines, that is, CXCL 5 . Bradykinin has pleiotropic actions, that is, decreased blood pressure, increased vascular permeability, and promotion of classical symptoms of inflammation such as vasodilation, hyperthermia, edema, and pain (warning signal). In addition, it has beneficial effects, that is, potent antithrombogenic, antiproliferative, and antifibrogenic effects .…”
Section: Physiological Action Of Acementioning
confidence: 99%